Is Educated Labor Really Productive? - Rr Retno Sugiharti; Fitrah Sari Islami; Octavia Laksmi Pramudiastuti (Economics Development Analysis Journal, 2021)
Improving the quality of human resources through education is believed to increase laborproductivity. The higher the investment in education, the greater the potential for someone to gainknowledge, expand access to jobs, and increase productivity. However, the increases in the numberof educated workforces, truly unbalanced with the increase with aggregate productivity. Thepurpose of this study is to analyze at which one of the levels of education has the greatestcontribution to increasing productivity. In order to bring the research in macro level, we usedMincer equation calibrated by Bils and Klenow (2000) to develop a human capital model. Thiskind of research formed in micro level and very rarely research is done at the macro level.Therefore, by using calibration from Bils and Klenow (1992), this study tries to bring the mincermodel to the macro level. This model estimates by panel regression method and cointegrationmethod (for identification long run existence) and using data from the period of 2010-2018. Theresults of the study show a positive integration between the level of education towards workproductivity. The fact that vocational education is aimed at preparing workforce has no significanteffect on aggregate productivity. The result driven us to conclusion that education has not beenconsidered a human capital factor but signaling factor; schooling level of labor was not a drivenfactor to labor productivity, but the years of experience did and labor is tended to taking educationjust for formal reason not for academic reason.